Introduction pages, Nova Geodesia 4(4), 2024 - Paul SESTRAS (Nova Geodesia)
Nova Geodesia (https://novageodesia.ro), Issue 4, Volume 4, 2024: The papers published in this issue represent interesting novelties in different topics of geodetic science or related fields. Nova Geodesia publishes significant papers in geodesy and close topics related to cartography, engineering projects and construction, planetology, hydrography, geography, sociodemographic factors, urban administration, planning and environment, landscape, biodiversity, and ecology. Among the exciting articles, we invite readers to find news about: Evaluating the performance of various models for deriving orthometric heights using Global Navigation Satellite System (GNSS) data; Carbon stocks under different land cover types in the Hallaydeghe wildlife reserve, northeastern Ethiopia; Sorghum (Sorghum bicolor) yield and water use efficiency depending on planting techniques and soil mulching in drought-prone areas, Babile District, Ethiopia; Colour selection in Lantana camara L. blooms: A study on butterfly attraction; Assessment of treatment water effects on macrobenthic invertebrates in an urban stream; Influence of geographical provenance, biostimulatory treatments and their interaction on the seed germination of Quercus robur L.